Microplastics comparison of indoor and outdoor air and ventilation rate effect in outskirts of the Seoul metropolitan city - Muhammad Jahanzaib; Shambhavi Sharma; Duckshin Park (Emerging Contaminants)
Microplastics in the air are becoming a concern, especially in indoor environments. Outdoor microplastics can travel from far spaces while indoor ones remain suspended and recirculate in the indoor environment. In this study, we collected air samples from the same buildings indoors and outdoors and observed the indoor microplastic concentration was 1.8 times higher than the outdoor. 24-hour sampling was performed with a mini-volume air sampler at the rate of 5 L/min. In this study, along with a comparison of indoor and outdoor concentrations, we also studied the microplastics' type size, and shape. We found that fiber-type microplastics account for nearly 90 % of the total and synthetic fibers. We also reported the 10 highest present microplastics are Polyethylene, Polyethersulfone, Polyamide, Polystyrene, Acrylic, Polyvinyl Chloride, Polytetrafluoroethylene, Alkyd, and Polyurethane. It is also observed the indoor ventilation rate plays a major role in the microplastic concentrations, long and periodic ventilation resulted in the lower concentration of the indoor microplastics. This study resulted in higher indoor air concentrations than outdoor and even in the outskirts of the metropolitan city which shows that indoor air concentrations are dependent on indoor sources and human activity.